SYSTEM OF FINANCIAL SECURITY: THE THEORETICAL FEATURES OF THE DEFINITION AND PLACE IN THE STRUCTURE OF THE ECONOMIC SECURITY OF THE ENTERPRISE - Майборода, Аліна (Socio-economic relations in the digital society, 2019)
The analysis and systematization of theoretical aspects of economic security was made and the place of financial security in it was determined. The main aspects of theoretical analysis of economic and fi nancial security, as well as their essential characteristics, are shown. The main approaches to the formation of the structure of economic security are considered. The schematic structure of the basic and essential elements of economic security is proposed, three important components are distinguished, which have a significant impact on the state of economic security of the subject of economic activity. The essence of the concept «financial security of the enterprise» was investigated, the classification of approaches for systematization of defi nitions, which was refl ected in the works of domestic and foreign scientists, was proposed. As a result, the essential characteristics of this concept are distinguished. The features of the categorical apparatus of the notion «fi nancial security» on micro, macro, and meso-level are considered. The necessity and expediency of introduction of fi nancial security system at the enterprise as the necessary tool of stability of its work is substantiated. Th e actual statement of this concept is proposed, which includes the characteristic features of the defi nition as a system and includes the most important, in our vision, administrative and functional elements ensuring a high level of fi nancial security in the enterprise. It also proved the necessity of introducing into the organizational structure of the company’s management of a separate subdivision exactly for the performance of the functions entrusted to it in relation to fi nancial security.